O papel da infraestrutura em modelos de crescimento macroeconômicos: Avaliaç\~ao de impacto a partir de metarregress\~ao - Bruno César Pino Oliveira De Araújo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– Infrastructure is traditionally considered a necessary condition for a country's economic development. However, despite so many arguments in favor of the importance of infrastructure for productivity, growth and welfare, the empirical literature on the impact of infrastructure is controversial. This article first presents a systematic review of the literature on empirical growth models that incorporate infrastructure among their production factors. From this, a meta-analysis of these articles is carried out, based on a technique known as meta-regression. The meta-regression comprised 52 parameters in 41 articles that use a comparable methodology between 1983 and 2006, and provides public capital elasticities ranging from 13.0% to 17.1% (with a sample average of 15.9%).
Keywords: E22; H54; 330; infrastructure; public capital; public investment; elasticity; meta-analysis; metaregression